Information needs and information seeking behaviour at the College of Medicine, The Sultan Qaboos University, Oman / Huda Sulaiman al-Haddabi - Huda Sulaiman , al-Haddabi (2005)
This study investigated information needs and information seeking behavior of students and academic staff at the Faculty of Medicine, the Sultan Qaboos University, Oman. The study also investigated the perceptions of respondents towards the performance of medical librarians, adequacy of the library collection, equipment and facilities. A questionnaire-based survey method was used for data collection. The instrument was adapted form previous studies on similar topics. The sample of respondents comprised 390 randomly selected undergraduate students, all 28 postgraduate students, and all 74 academic staff. The response rate was 63.4% (i.e. 241 questionnaires). The findings showed that more than 72.5% of the respondents were skilled in computer use. At least 34% of respondents preferred the Internet as source of information, followed by 30% who preferred journal articles, and 25% who preferred conference papers. A majority (54.7%) of the respondents considered the World Wide Web to be the most useful information source. All the academic staff sought information to conduct research and publish, while students respondents were seeking information for class assignments. A large majority (80.9%) of the respondents frequently used “subject” as access point. Librarians were "sometimes" consulted for help in seeking information, and 76.8% of the respondents rated librarians’ performance as being good. Similarly, 79.6% of the respondents preferred visiting the library personally when they needed information, and more than 90% of them were satisfied with the library. The findings are useful in understanding the information needs and information seeking behaviour and developing strategic plans for the library and information services at the College of Medicine, the Sultan Qaboos University, Oman.